Self-propelled manganese oxide-based catalytic micromotors for drug delivery. Issue 70 (11th July 2016) - Wang, Linlin; Chen, Jun; Feng, Xiaomiao; Zeng, Wenjin; Liu, Ruiqing; Xiujing Lin,; Ma, Yanwen; Wang, Lianhui
Abstract : A novel self-propelled drug delivery vehicle was developed to capture and transport an anticancer drug through electrostatic interactions. Abstract : A manganese oxide-based catalytic tubular micromotor (PEDOT/MnO2 ) is described that displays effective autonomous motion in hydrogen peroxide with high speed (318.80 µm s −1 ) and can operate in very low levels of fuel, down to 0.4%. The polymer bilayer micromotor also exhibits efficient locomotion in different biological media including bovine serum albumin and bovine serum. Moreover, the micromotor is applied to deliver a chemotherapeutic anticancer drug, camptothecin, using electrostatic interactions, offering considerable potential for diverse clinical and biomedical applications such as drug delivery for theranostic microsystems.